Beginning Android - Murphy, Mark L. (Apress, 2012)
If you are interested in programming for Android, you will need at least basic understanding of how to program in Java. Android programming is done using Java syntax, plus a class library that resembles a subset of the Java SE library (plus Android-specific extensions). If you have not programmed in Java before, you probably should learn how that works before attempting to dive into programming for Android. The book does not cover in any detail how to download or install the Android development tools, either the Eclipse IDE flavor or the standalone flavor. The Android Web site2 covers this quite nicely. The material in the book should be relevant whether you use the IDE or not. You should download, install, and test out the Android development tools from the Android Web site before trying any of the examples listed in this book.